Personality and coping with a low-control situation: Cross-lagged latent variable analysis - Buško, Vesna (Array, 2008)
The study aimed to test the hypothesized nature and directions of personality, appraisals, and coping relationships. The data were collected on a sample of 421 basic military trainees within a follow-up study of coping with low-control stress. Structural equation models used to test hypothesized mediation effects of cognitive appraisals were specified within a 2-wave cross-lagged panel design, with stationarity assumed on theoretical grounds. Partial mediation effects of event stressfulness were confirmed for emotion-focused coping only. The results were compared with those obtained by structural equation analyses done within different methodological framework but tested against the same data sets.